2021
DOI: 10.1051/mfreview/2021003
|View full text |Cite
|
Sign up to set email alerts
|

Micro milling process modeling: a review

Abstract: The trend towards miniature manufacturing in high technological fields like bioengineering, electronics and aerospace has increased dramatically over the last decade. Many methods of micro manufacturing have been researched and applied to manufacture small scale components. Among these manufacturing methods micro-mechanical machining methods have shown themselves to be attractive alternatives. Micro milling is one of the most frequently used micro-mechanical machining method with high potential for the precise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Simulation and modeling: Advancements in simulation software have enabled accurate prediction of tool behavior, cutting forces, and surface quality during micromilling. These models aid in optimizing tool paths, reducing vibration, and improving dimensional accuracy [55,56].…”
Section: Advances and Solutionsmentioning
confidence: 99%
“…Simulation and modeling: Advancements in simulation software have enabled accurate prediction of tool behavior, cutting forces, and surface quality during micromilling. These models aid in optimizing tool paths, reducing vibration, and improving dimensional accuracy [55,56].…”
Section: Advances and Solutionsmentioning
confidence: 99%
“…Very large spindle speed is required to maintain the cutting speed, due to small tool diameter. Tool deflection in smaller tools is a significant problem [29]. In micro turning, workpiece loses rigidity and deflect due to thin cross-section.…”
Section: µMilling/ µTurningmentioning
confidence: 99%
“…Due to the high number of studies on chatter and the relevant areas, there have been diverse reviews published with related topics to the study of chatter detection, as follows. Chatter in milling literature has been reviewed in three different articles by Quintana [1,9,11], while Wu et al reviewed chatter in thin-wall machining [12]; robotic machining studies have been discussed by Pan et al and Yuan et al [13,14], and Yan et al focused on blade milling [15], along with other reviews on the mathematical models of chatter and machining dynamics by Altintas et al [3,16], Mamedov et al [17] and Insperger et al [18], and the review on vibration measurement by Murthy et al [19]. Besides, Teti et al [20] reported strategies for process monitoring, while Jardine et al [21] reviewed the diagnostics of mechanical systems.…”
Section: Introductionmentioning
confidence: 99%